2021
DOI: 10.1111/cts.12996
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of hemoglobin level and plasma coproporphyrin‐I concentrations as an endogenous probe for phenotyping OATP1B

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(106 reference statements)
0
3
1
Order By: Relevance
“…In all patients, the male to female ratio was 40 to 34, and the most frequent underlying disease was nephrotic syndrome, followed by organ transplanta- 1121.6 ng/mL, respectively. CP-I concentration in patients taking CyA was higher than that in healthy volunteers (0.48 ± 0.17 ng/mL) reported by Suzuki et al 23 Median CP-I concentrations in patients with nephrotic syndrome, organ transplantation, and aplastic anaemia or pure red-cell aplasia were 1.19, 1.17 and 1.02 ng/mL, respectively, suggesting no difference among underlying diseases. The concentrations of CyA and CP-I were significantly higher in peak samples than in trough samples (CyA: P < .001, CP-I: P < .001), while CMPF concentration did not differ between the 2 groups.…”
Section: Patient Characteristicscontrasting
confidence: 52%
“…In all patients, the male to female ratio was 40 to 34, and the most frequent underlying disease was nephrotic syndrome, followed by organ transplanta- 1121.6 ng/mL, respectively. CP-I concentration in patients taking CyA was higher than that in healthy volunteers (0.48 ± 0.17 ng/mL) reported by Suzuki et al 23 Median CP-I concentrations in patients with nephrotic syndrome, organ transplantation, and aplastic anaemia or pure red-cell aplasia were 1.19, 1.17 and 1.02 ng/mL, respectively, suggesting no difference among underlying diseases. The concentrations of CyA and CP-I were significantly higher in peak samples than in trough samples (CyA: P < .001, CP-I: P < .001), while CMPF concentration did not differ between the 2 groups.…”
Section: Patient Characteristicscontrasting
confidence: 52%
“… 22 , 39 In one study, blood hemoglobin level was associated with plasma CPI levels, but no independent association between hemoglobin and CPI concentrations was found after adjusting for sex. 39 Similarly, in our study, blood hemoglobin concentration showed no independent association with CPI or CPIII concentration in the final linear regression model including sex as an independent variable. On the other hand, the concentrations of some other endogenous OATP1B1 substrates have also shown similar sex‐related differences.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with previous data regarding CPI, 22 we saw on average 30% higher plasma CPI and CPIII concentrations in men than in women. These sex‐related differences in plasma CP levels have been suggested to be at least partly due to a higher heme synthesis rate in men 22,39 . In one study, blood hemoglobin level was associated with plasma CPI levels, but no independent association between hemoglobin and CPI concentrations was found after adjusting for sex 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation